Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1044/1092-4388(2008/06-0193)
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Speech Timing in Young Children Later Found to Have Reading Disability

Abstract: The results are discussed in terms of speech and language formulation. Phonetic plans may be shorter and/or less specified in children with RD, surfacing as slow, short speaking turns with increased pausing relative to articulation. This explanation is consistent with several accounts of RD and provides a perspective on how speech and language deficits may manifest during spontaneous verbal interactions between young children and adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…Neither study included rise-time measures; nevertheless, both identified a range of neonate and infant auditory weaknesses using electroencephalography (EEG) that predicted later phonological awareness and reading ability [93][94][95] . A small-scale family-risk longitudinal study in English children revealed timing difficulties in syllable production for the at-risk children at the ages of two and three 96 .…”
Section: Amplitude Modulation (Rise-time) Deficitmentioning
confidence: 99%
“…Neither study included rise-time measures; nevertheless, both identified a range of neonate and infant auditory weaknesses using electroencephalography (EEG) that predicted later phonological awareness and reading ability [93][94][95] . A small-scale family-risk longitudinal study in English children revealed timing difficulties in syllable production for the at-risk children at the ages of two and three 96 .…”
Section: Amplitude Modulation (Rise-time) Deficitmentioning
confidence: 99%
“…For example, both children and adults with dyslexia have difficulties in recognizing syllable stress [11], [12], [13], [14] (identifying strong versus weak syllables). Studies of 2- and 3-year-olds at family risk for dyslexia have indicated speech timing difficulties in children who later present with reading difficulties, suggesting that difficulties are found in speech production as well as speech perception [15], although motor production difficulties as distinct from timing difficulties are a potential confound for the production data. Children who later turned out to have dyslexia produced significantly fewer syllables per second in early childhood (4.8 at age 3 compared to 7.1 for non-risk children) and paused for longer between articulations, suggestive of early syllable-level deficits.…”
Section: Introductionmentioning
confidence: 99%
“…B. Smith et al, 2006;A. B. Smith, Lambrecht Smith, Locke, & Bennett, 2008;Fawcett & Nicolson, 2002).…”
mentioning
confidence: 97%